The Role of Actuarial Accounting in Achieving Financial Sustainability - Hussien Sabea Khamees (International Journal on Economics, Finance and Sustainable Development, 2026)
This study aims to clarify actuarial accounting, the actuary accountant, and their role in enhancing the financial sustainability of companies. The research discusses the significant role of actuarial accounting in strengthening corporate sustainability, particularly in companies with future obligations, due to its importance in identifying future risks. The study concluded that actuarial accounting plays an effective role in increasing companies’ ability for long-term financial planning, which enhances corporate sustainability. Furthermore, actuarial accounting has the capability to assess future risks through the use of statistical and historical data to predict future financial events. The study recommends expanding the reliance on actuary accountants within companies in order to improve long-term financial planning capabilities. It also recommends involving actuary accountants in decision-making processes because of their role in determining the optimal allocation of resources.